Relationship of node number with days to flowering and yield traits in castor (Ricinus communis L.) hybrids under rainfed and irrigated conditions: RELATIONSHIP OF NODE NUMBER WITH DAYS TO FLOWERING AND YIELD TRAITS IN CASTOR HYBRIDS - T MANJUNATHA; C LAVANYA; S SENTHILVEL; M P PATEL; K T RAMYA; C SARADA (Journal of Oilseeds Research, 2020)
A set of 150 hybrids were evaluated in augmented design with three checks under rainfed and irrigated conditions at research farm of ICAR-Indian Institute of Oilseeds Research, Telangana and Anand Agricultural University, Anand, Gujarat to understand the environmental effect on node number and its influence on yield attributing traits. Results indicated that the number of nodes to the base of primary spike (NN) influenced not only days to 50% flowering (DFF) and yield traits but also plant canopy particularly under rainfed conditions. Under both rainfed and irrigated conditions, the genotypes with high node number, in general, recorded increased plant height, days to 50% flowering (DFF), primary spike length, and seed yield/plant. Under rainfed conditions, most of the early hybrids with NN